Compact Slot Antenna Integrated with a Photovoltaic Cell - Ali, Ahmed; Wang, Heesu; Yun, Yeojun; Lee, Jaejin; Park, Ikmo (Journal of Electromagnetic Engineering and Science, 2020)
This paper presents a compact low-profile slot antenna integrated with a photovoltaic cell. The photovoltaic cell consists of a top metal grid, gallium arsenide substrate, and metallic bottom contact. The metallic bottom contact was used as a ground plane where the slot was etched for resonance. A second substrate was placed under the ground plane, and a 50 Ω microstrip line was printed on its bottom side to excite the slot. A chip inductor was used as a radio frequency (RF) choke in the alternating current blocking circuit to suppress RF current leakage towards the photovoltaic cell. Hence, the proposed antenna has a unique feature of functioning simultaneously as a photovoltaic cell and an antenna. The overall dimensions––25 mm × 31.75 mm × 0.893 mm (0.48λo × 0.61λo × 0.017λo at 5.77 GHz)––of the photovoltaic cell-integrated slot antenna structure can be used effectively with Internet of Things devices.
Keywords: Compact Antenna; Integrated Antenna; IoT Devices; Photovoltaic Cell; Slot Antenna